Submacular Hemorrhage: Visual Outcomes and Prognostic Factors. Issue 2 (March 2018) - Kunavisarut, Paradee; Thithuan, Tipparut; Patikulsila, Direk; Choovuthayakorn, Janejit; Watanachai, Nawat; Chaikitmongkol, Voraporn; Pathanapitoon, Kessara; Rothova, Aniki
Abstract : Purpose: : To describe causes, visual outcomes, and prognostic factors in patients with submacular hemorrhage (SMH). Design: : Retrospective case review. Methods: : We performed a retrospective review of SMH with a size of at least 1 disc diameter. SMH causes were classified into 3 groups: 1) neovascular age‐related macular degeneration (nAMD), 2) polypoidal choroidal vasculopathy (PCV), and 3) other miscellaneous causes. Results: : Ninety‐eight eyes of 98 patients were included. Based on clinical presentation and indocyanine green angiography (ICGA), the diagnoses of PCV (59%), nAMD (31%), and miscellaneous other causes (10%) were made. PCV patients were younger ( P = 0.005) and had larger SMH size than nAMD patients ( P = 0.008). Poor visual outcome [>1.0 logarithm of the minimum angle of resolution (logMAR)] at 6 months was associated with low initial visual acuity (VA; >1.0 logMAR; P = 0.002) and with the diagnosis of nAMD ( P = 0.02). In addition, limited visual outcomes were noted for patients older than 65 years and those with persistent SMH for at least 2 months. Conclusions: : PCV was the most common cause of SMH in Thailand. ICGA represented a valuable tool for the diagnosis. Visual outcomes were limited for patients with nAMD and for patients who presented with poor initial VA.